Penyelesaian Masalah TSP Pada Rute Kunjungan ATM Dengan Pendekatan Heuristik (Tabu Search) - Jhon Pontas Simbolon; Muhammad Zarlis (STIKOM Tunas Bangsa Pematangsiantar, 2017)
Determination of optimum route is a problem that can be found in a variety of activities. Principal of the problem is how to organize the trip so the distance is the minimum distance that the optimum is best found on a map or graph. There are many algorithms available to solve them. Algorithm is divided into two parts, the exact methods and heuristic methods. Heuristic method is considered the best method because it can work quickly. Tabu search is a heuristic method that is often used in solving optimization problems. The algorithm works by improving a solution by using memory to avoid that the search process does not get stuck at a local optimum value by rejecting new solutions that may be in memory (taboo) so that the new solution will be more dispersed. The author will implement a tabu search algorithm to provide a better alternative solution to solve the problems of the effectiveness of the distribution of charging money at the ATM machine.